The Photographer-Flâneur as Facilitator of Urban Connectivity in John Edgar Wideman's Two Cities. Issue 2 (15th March 2019) - Valkeakari, Tuire
ABSTRACT: John Edgar Wideman's Two Cities oscillates dialectically between urban dystopianism and more optimistic perspectives, ultimately representing what Joseph R. Winters calls a "melancholic hope." Wideman peoples his seemingly bleak Philadelphia and Pittsburgh cityscapes with protagonists who, despite their urban isolation and existential disenchantment, still pursue interpersonal connection. This article focuses on the novel's photographer-flâneur, Martin Mallory, a physically and emotionally traumatized African American World War II veteran. Two Cities modifies the Baudelairian/Benjaminian trope of the well-off, gentlemanly, and leisurely writer-flâneur by casting Mallory—a marginalized, indigent, and infirm photographer-flâneur—as an agent of human connectivity in the novel's black Pittsburgh. Despite both witnessing and embodying trauma, Mallory facilitates connection and reconciliation, albeit in ways representing modest beginnings rather than spectacular triumphs. Wideman incorporates a glimmer of utopian hope into certain aspects of Mallory's Giacomettian approach to his photography and into plot developments that highlight Mallory's unlikely role as a creator of community.